The role of social assistance in reducing poverty and inequality in Asia and the Pacific. - Barrientos, Armando (Sustainable development working papers., 2019)
The analysis is divided into three main sections. First, it reviews long standing and emerging challenges to social protection in the region: poverty and inequality, demographic change, inclusive growth, and environmental change. Second, it reviews the provision of social assistance: spending, programming, reach, and distribution. Third, it examines key issues shaping the development of social assistance: equity, social investment, and sustainable financing.